1985
DOI: 10.1289/ehp.60-1568568
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of alkylmercuric compounds with sodium selenite. III. Biotransformation, levels of metallothioneinlike proteins and endogenous copper in some tissues of rats exposed to methyl or ethylmercuric chloride with and without sodium selenite.

Abstract: The biotransformation efficiency of alkylmercurial compounds was studied in rat liver, kidneys, blood, and brain after 2-week administration of methylmercuric chloride (MeHg) and ethylmercuric chloride (EtHg) at doses of 0.25 or 2.5 mg Hg/kg, alone or in combination with sodium selenite (Se) at a level of 0.5 mg Se/kg. Simultaneously, the level of metallothioneinlike proteins (MTP) and endogenous copper (Cu) was monitored in tissues of control rats and intoxicated rats. Regardless of the dose, the highest conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…6) points to a possible participation of metallothionein-like proteins in this process (15,68). That is probably due to the higher efficiency of biotransformation of methylmercury to inorganic mercury in rat kidneys as compared with liver (58,65,69,70); this process seems to be strictly dependent on the dose of methylmercury which has been taken into account in our further studies (71).…”
Section: Discussionmentioning
confidence: 91%
“…6) points to a possible participation of metallothionein-like proteins in this process (15,68). That is probably due to the higher efficiency of biotransformation of methylmercury to inorganic mercury in rat kidneys as compared with liver (58,65,69,70); this process seems to be strictly dependent on the dose of methylmercury which has been taken into account in our further studies (71).…”
Section: Discussionmentioning
confidence: 91%
“…It is widely believed that only the inorganic mercuric ion, Hg 2+, is capable of eliciting the metallothionein response (Chmielnicka & Brzeznicka, 1978), and that, in rats dosed with methylmercury, the appearance of LEYSHON-S~RLAND, JASANI and MORGAN metallothionein within the kidney is due to the biotransformation of the alkyl mercurial to the inorganic form (Brzeznicka & Chmielnicka, 1985). In the brain, the inorganic mercury content amounted to only 15% of the total mercury accumulated in the tissue (Brzeznicka & Chmielnicka, 1985). Since Baatrup et al (1986) reported that only inorganic mercury is located histochemically by silver physical development, it would appear that a substantial level of biotransformation has taken place, at least in some cells of the cerebellum.…”
Section: Figs 1~mentioning
confidence: 99%